Effects of azo dye on simultaneous biological removal of azo dye and nutrients in wastewater. Issue 8 (15th August 2018) - Chen, Aihui; Yang, Bairen; Zhou, Yuanqiang; Sun, Yuze; Ding, Cheng
Abstract : The potential disrupting effects of Azo dye on wastewater nutrients removal deserved more analysis. In this study, 15 days exposure experiments were conducted with alizarin yellow R (AYR) as a model dye to determine whether the dye caused adverse effects on biological removal of both the dye and nutrients in acclimated anaerobic–aerobic–anoxic sequencing batch reactors. The results showed that the AYR removal efficiency was, respectively, 85.7% and 66.8% at AYR concentrations of 50 and 200 mg l −1, while higher AYR inlet (400 mg l −1 ) might inactivate sludge. Lower removal of AYR at 200 mg l −1 of AYR was due to the insufficient support of electron donors in the anaerobic process. However, the decolorized by-products p -phenylenediamine and 5-aminosalicylic were completely decomposed in the following aerobic stage at both 50 and 200 mg l −1 of AYR concentrations. Compared with the absence of AYR, the presence of 200 mg l −1 of AYR decreased the total nitrogen removal efficiency from 82.4 to 41.1%, and chemical oxygen demand (COD) removal efficiency initially decreased to 68.1% and then returned to around 83.4% in the long-term exposure time. It was also found that the inhibition of AYR, nitrogen and COD removal induced by a higher concentration of AYR was due to the increased intracellular reactive oxygen species production, which caused the rise of oxidation–reduction potential value and decreased ammonia monooxygenase and nitrite oxidoreductase activities.